Assortative matching and search with labour supply and home production - Nicolas Jacquemet; Jean-Marc Robin (Centre for Microdata Methods and Practice (cemmap), 2013)
We extend the search-matching model of the marriage market of Shimer and Smith (2000) to allow for labor supply and home production. We characterize the steadystate equilibrium when exogenous divorce is the only source of risk. We study nonparametric identification using cross-section data on wages and hours worked, and we develop a nonparametric estimator. The estimated matching probabilities that can be derived from the steady-state flow conditions are strongly increasing in male and female wages. We estimate the expected share of marriage surplus appropriated by each spouse as a function of wages. The model allows to infer the specialization of female spouses in home production from observations on wages and hours worked.
Keywords: C78; D83; J12; J22; 330; Search-matching; sorting; assortative matching; collective labor supply; structural estimation